Security returns and tax aversion bias: Behavioral responses to tax labels - Kay Blaufus; Axel Möhlmann (Arbeitskreis Quantitative Steuerlehre (arqus), 2012)
This paper studies behavioral responses to taxes in financial markets. It is motivated by recent puzzling empirical evidence of taxable municipal bond yields significantly exceeding the level expected relative to tax exempt bonds. A behavioral explanation is a tax aversion bias, the phenomenon that people perceive an additional burden associated with tax payments. We conduct market experiments on the trading of differently taxed and labeled securities. The data show an initial overvaluation of tax payments that diminishes when subjects gain experience. The tax deduction of expenses is valued more than an equivalent tax exemption of earnings. We find that the persistence of the tax aversion bias critically depends on the quality of feedback. This suggests that tax aversion predominantly occurs in one-time, unfamiliar financial decisions and to a lesser extent in repetitive choices.
Keywords: D03; G32; H20; H3; 330; Behavioral finance; Behavioral taxation; Investor psychology; Tax aversion; Experiment